2021
DOI: 10.1016/j.jclinepi.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The potential of prediction models of functioning remains to be fully exploited: A scoping review in the field of spinal cord injury rehabilitation

Abstract: Objective: The study aimed to explore existing prediction models of functioning in spinal cord injury (SCI). Study Design and Setting: The databases PubMed, EBSCOhost CINAHL Complete , and IEEE Xplore were searched for relevant literature. The search strategy included published search filters for prediction model and impact studies, index terms and keywords for SCI, and relevant outcome measures able to assess functioning as reflected in the International Classification of Functioning, Disability and Health (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
5
0
2
Order By: Relevance
“…These outcome measures form the basis for documenting rehabilitation outcomes in terms of rehabilitation duration and can then be used to make informed decisions about appropriate service delivery. In addition, they are needed to calculate rehabilitation trajectories that can provide information about expected outcomes and lead to better rehabilitation planning ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These outcome measures form the basis for documenting rehabilitation outcomes in terms of rehabilitation duration and can then be used to make informed decisions about appropriate service delivery. In addition, they are needed to calculate rehabilitation trajectories that can provide information about expected outcomes and lead to better rehabilitation planning ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Hodel et al 22 explored databases such as EBSCOhost CINAHL Complete, PubMed, and IEEE Xplore, to find all publications that developed prediction models for spinal cord injury (SCI). The searches showed that twelve different predictive models were developed in seven unique studies to predict the following clinical outcomes in patients with SCI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2021, Hodel et al 27 explored databases such as EBSCOhost CINAHL Complete, PubMed, and IEEE Xplore, to nd all publications that developed prediction models for spinal cord injury (SCI). The searches showed that twelve different predictive models were developed in seven unique studies to predict the following clinical outcomes in patients with SCI.…”
Section: Literature Reviewmentioning
confidence: 99%